Exact Solvability Conditions for the Cauchy Problem for Systems of First-Order Linear Functional-Differential Equations Determined by $(σ_1, σ_2, ... , σ_n; τ)$-Positive Operators - Ronto, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We obtain new sufficient conditions under which the Cauchy problem for a system of linear functional-differential equations is uniquely solvable for arbitrary forcing terms. The conditions established are unimprovable in a certain sense.